2016
DOI: 10.1097/cin.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Patient Education in Mobile Platform for Patients With Heart Failure

Abstract: Health education is an important component of multidisciplinary disease management of heart failure. The educational information given at the time of discharge after hospitalization or at initial diagnosis is often overwhelming to patients and is often lost or never consulted again. Therefore, the aim of this developmental project was to embed interactive heart failure education in a mobile platform. A patient-centered approach, grounded on several learning theories including Mayer's Cognitive Theory of Multim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 37 publications
0
53
0
Order By: Relevance
“…Overall, 115 papers have reported on the use of smartphone apps for patient education. Of these, 3 studies targeted cardiovascular disease, including cardiac rehabilitation, coronary artery disease, and heart failure [ 36 - 38 ]; 3 studies focused on overweight adults and physical activity [ 30 , 31 , 39 ]; 2 smartphone apps reported on asthma [ 40 , 41 ]; and 3 studies targeted mental illnesses such as depression and bipolar disorder [ 32 , 33 , 42 ]. Diabetes was the focus of 2 mobile-based interventions [ 29 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 115 papers have reported on the use of smartphone apps for patient education. Of these, 3 studies targeted cardiovascular disease, including cardiac rehabilitation, coronary artery disease, and heart failure [ 36 - 38 ]; 3 studies focused on overweight adults and physical activity [ 30 , 31 , 39 ]; 2 smartphone apps reported on asthma [ 40 , 41 ]; and 3 studies targeted mental illnesses such as depression and bipolar disorder [ 32 , 33 , 42 ]. Diabetes was the focus of 2 mobile-based interventions [ 29 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 1 study reported the feasibility of engaging adolescents with smartphone education [ 44 ], and 1 study focused on parental education and engagement [ 28 ]. Papers included in the review reflected study designs across the research spectrum including RCTs (n=6) [ 28 - 33 ] and case-control (n=1) [ 39 ], proof-of-concept (n=2) [ 36 , 40 ], and feasibility and pilot studies (n=5) [ 37 , 41 - 44 ]. One paper did not report the design of the study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, it is characterized as a printed material that contributes to the shared construction of knowledge and allows the users of the health system and their families a posterior reading. Thus, the primer can reinforce the verbal guidelines, acting as a guide in cases of doubt and assisting in the decision-making (8)(9) . Despite its practical purpose, we highlight that educational technologies must be constructed from theoretical approaches (10) .…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Other interventions that have been tested for effects to improve patient outcomes in HF include those aimed at improving cognitive function. In preliminary studies, cognitive training led to small improvements in cognitive function, 41,42 as well as positive effects on engagement in HF self-care 43 and functional outcomes such as instrumental activities of daily living (e.g., medication taking, grocery shopping) that may result in reduced healthcare costs. 44 In addition, family relationships among patients with HF and their caregivers were examined in several studies; investigators described both positive and neutral results of family based interventions.…”
Section: Nursing Interventions To Improve Outcomesmentioning
confidence: 99%